A Case of Bilateral Retinal Hemorrhage with Cotton Wool Spot Following Viper Bite (Bangladesh Journal of Medical Science, 2015)
A 38 years male, admitted in the department of Internal Medicine with a history of snake bite in his left lower leg during agriculture work. He was treated with anti snake venom after admission. He had history of dimness of vision in both eyes. On examination, swelling and subcutaneous hemorrhage was noted in his left leg. His best corrected visual acuity (BCVA) was 6/60 in the both eyes. Fundus examination with 90 D lens and Indirect Ophthalmoscopy of both eyes showed retinal hemorrhage with cotton wool spots. Blood tests revealed increased titers of D-dimer and fibrin degradation products. The patient was followed up regularly at 2 weeks interval and BCVA and Fundus examination was carried out. At the end of 10 weeks, retinal hemorrhages had significantly cleared in both eyes with improvement of vision in both eyes (BCVA of right eye at last follow-up 6/6 and left eye 6/9).Bangladesh Journal of Medical Science Vol.14(3) 2015 p.297-298